Soil carbon stocks and nitrous oxide emissions of pasture systems in Orinoquía region of Colombia: Potential for developing land-based greenhouse gas removal projects - Costa, Ciniro; Villegas, Daniel M.; Bastidas, Mike; Matiz-Rubio, Natalia; Rao, Idupulapati; Arango, Jacobo (Frontiers in Climate, 2022)
Improving grassland conditions under grazing has the potential not only to accumulate carbon in soils, but also to reduce nitrous oxide (N2O) emissions from animal urine deposition. However, measurements in developing countries are still scarce. In the Orinoquia region, permanent grasslands (PG; this unimproved, native pasture is considered as at some state of degradation) based on unimproved grasses are found due to extensive, inefficient grazing combined with annual burning of pastures. We hypothesized that, compared to PG, improved grasslands (IG) managed through rotational grazing of introduced, productive and deep-rooted pasture grass species promote soil organic carbon (SOC) accumulation and reduce N2O emission from urine deposited by grazing cattle. We determined SOC and N2O emissions from urine deposited on soils in an area of PG and in a 6.5 year-old IG area of Urochloa (Syn. Brachiaria) humidicola grass pasture in a beef cattle ranch in Orinoquía region (Colombia). In both areas, we sampled soil for chemical/physical analysis, and measured N2O emissions by simulating urine deposition over 21 days. We applied two-way analysis of variance considering pasture type and soil depth as fixed factors. Estimated SOC stocks (0–100 cm) were in the range of 224.8 Mg C ha−1 for the PG and 259.0 Mg C ha−1 for the IG, with a significant (p < 0.05) average accumulation of 2.0 Mg C ha−1 y−1 (0–20 cm) in the IG area. N2O emissions were 10 times lower in the IG compared to the PG. The introduction of U. humidicola grass influenced SOC accumulation probably through its more abundant root system and greater turnover together with higher (14%) forage dry matter production compared to PG. The reduced N2O emissions observed from urine patches in IG were attributed to biological nitrification inhibition ability and greater nitrogen uptake of U. humidicola grass. Compared to the reference default value of IPCC for, the SOC stock found in PG was almost 40% higher, whereas the N2O emission factor (5%) was within the uncertainty range (0.7–6%). The Orinoquía region shows significant potential for SOC storage and reduced N2O emissions in improved pastures with deep root systems. Thus, scaling the implementation of land-based SOC storage practices/projects could significantly contribute to reducing net emissions from beef production from this region.